The Effects Of Arsenic Accumulation In Clarias Gariepinus On The Activity Of The Enzyme Catalase (International Journal of Food and Nutritional Sciences, 2022)
Due to increased pesticide, sewage, and untreated industrial effluent discharges, heavy metals are prevalent environmental pollutants. Arsenic is one of these heavy metals, and it may be found in groundwater, warm springs, rivers, and lakes as well as in saltwater. The goal of the current research was to determine how arsenic buildup affected the catalase activity in the muscular tissues of fingerling African catfish Clarias gariepinus. The goal of the current investigation was to determine if calcium carbonate has any protective effects against arsenic's high toxicity to Clarias gariepinus. Some blood parameters and the hepatosomatic index (HSI) were elevated in fish exposed to arsenic spotlight, but the gonadosomatic index (GSI) and the intestinal index (ISI) were lowered. Fish exposed to arsenic showed plasma concentrations that were considerably higher than those of unsaturated fish, total bilirubin, direct bilirubin, total lipids, glucose, and total protein. Evidence suggests that arsenic poisoning causes an extreme upsurge in ALT, AST, and LDH, EC 1.1.1.27, as well as total protein and glycogen levels in these organs. Histological examination revealed degenerative changes in both the liver and the gills as a result of exposure to arsenic. Most of the arsenic-induced changes may be reversed by liming with calcium carbonate, especially in fish exposed to 1/20 LC50 of arsenic. Therefore, it could be viable to strengthen C. gariepinus with calcium carbonate to shield it against arsenic poisoning.